Association of Thromboxane Generation With Survival in Aspirin Users and Nonusers - Rade, Jeffrey J; Barton, Bruce A; Vasan, Ramachandran S; Kronsberg, Shari S; Xanthakis, Vanessa; Keaney, Jr, John F; Hamburg, Naomi M; Kakouros, Nikolaos; Kickler, Thomas A (Journal of the American College of Cardiology, 2022)
Persistent systemic thromboxane generation, predominantly from nonplatelet sources, in aspirin (ASA) users with cardiovascular disease (CVD) is a mortality risk factor. This study sought to determine the mortality risk associated with systemic thromboxane generation in an unselected population irrespective of ASA use. Stable thromboxane B metabolites (TXB -M) were measured by enzyme-linked immunosorbent assay in banked urine from 3,044 participants (mean age 66 ± 9 years, 53.8% women) in the Framingham Heart Study. The association of TXB -M to survival over a median observation period of 11.9 years (IQR: 10.6-12.7 years) was determined by multivariable modeling. In 1,363 (44.8%) participants taking ASA at the index examination, median TXB -M were lower than in ASA nonusers (1,147 pg/mg creatinine vs 4,179 pg/mg creatinine; P < 0.0001). TXB -M were significantly associated with all-cause and cardiovascular mortality irrespective of ASA use (HR: 1.96 and 2.41, respectively; P < 0.0001 for both) for TXB -M in the highest quartile based on ASA use compared with lower quartiles, and remained significant after adjustment for mortality risk factors for similarly aged individuals (HR: 1.49 and 1.82, respectively; P ≤ 0.005 for both). In 2,353 participants without CVD, TXB -M were associated with cardiovascular mortality in ASA nonusers (adjusted HR: 3.04; 95% CI: 1.29-7.16) but not in ASA users, while ASA use was associated with all-cause mortality in those with low (adjusted HR: 1.46; 95% CI: 1.14-1.87) but not elevated TXB -M. Systemic thromboxane generation is an independent risk factor for all-cause and cardiovascular mortality irrespective of ASA use, and its measurement may be useful for therapy modification, particularly in those without CVD.